The Rise and Fall of an Ontario Business Dynasty: William Kennedy & Sons and its successors, 1857-1997 - Fleming, Keith (Ontario History)

(untitled) (The Ontario Historical Society, 2012)
Between 1857 and 1951, the Owen Sound firm of William Kennedy & Sons was transformed by three successive generations of the Kennedy family into a dynasty. As a supplier of industrial equipment to the agricultural, milling, mining, railway, marine, hydro-electric, and pulp and paper sectors across Canada and internationally, “Kennedy's”  became a model of entrepreneurialism despite challenging the conventional wisdom that success depended upon economies of scale generated by product specialization. Originally, Kennedy's strength was its owners' determination to harness their craftsmen's ingenuity in making a plethora of products. After it became a branch plant of multinational corporations and was forced to focus increasingly on a single product line, the firm commenced a protracted and ignominious slide ending in bankruptcy in 1997. The history of William Kennedy & Sons is a rare account of how a medium-sized manufacturer conducted business over 140 years. It also provides a revealing look at the entrepreneurial spirit behind the creation of a once imposing, but now much diminished, industrial Ontario.